PENGARUH INFEKSI Toxoplasma gondii TERHADAP GAMBARAN LEUKOSIT DAN TOTAL PROTEIN PLASMA PADA AYAM PEDAGING - , IKROM; , drh. Dwi Priyowidodo, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Toxoplasmosis is a zoonotic disease that is spread all over the world . The cases of toxoplasmosis in animals and humans in Indonesia is very high, the prevalence of serological toxoplasmosis in humans 40-85 % , while in the animals have ranged between 5-80 %. High incidence of toxoplasmosis and negative impacts that result in economic losses and decreased production become particular concern that needs to be carried out a study of toxoplasmosis in broiler chickens. Transmission in broiler chickens often occur because the nature of chickens are consuming grass or small stones contaminated with cat feces are disposed in any places. Toxoplasma gondii infects all stem cells except erythrocytes. The research aims to determine the effect of T.gondii infection on the representation of the total leukocytes and plasma proteins in broilers that in infection with T.gondii as much as 500,000 takizoit at each chicken. Research using 36 broiler chickens were divided into 3 groups. The A group are infected by 500,000 takizoit per intravenous chickens, and The B group are infected via subcutaneous.Two chickens are taken blood sampling are performed on days 2,4,8,16,18, and 26 post-infection through intrakardia. Blood tests carried out in the Laboratory of Clinical Pathology, Faculty of Veterinary Medicine UGM. Data obtained were statistically analyzed by ANOVA. The results showed a decreased the total number of leukocytes (9312,50 sel/Î¼l) but not significant (p>0,05) and decreased of total plasma proteins (1,833 g/dL) also not significant (p>0,05).